2010
DOI: 10.1124/dmd.110.035808
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Novel Human Pregnane X Receptor Activators among Prescribed Drugs via Ligand-Based Virtual Screening

Abstract: ABSTRACT:Human pregnane X receptor (hPXR) plays a key role in regulating metabolism and clearance of endogenous and exogenous substances. Identification of novel hPXR activators among commercial drugs may aid in avoiding drug-drug interactions during coadministration. We applied ligand-based computational approaches for virtual screening of a commonly prescribed drug database (SCUT). Bayesian classification models were generated with a training set comprising 177 compounds using Fingerprints and 117 structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…In brief, the pharmacophore protocol embedded in Discovery Studio (DS) software suite (version 3.0; Accelrys; San Diego, CA) was used to generate a qualitative CAR pharmacophore based on 17 previously reported hCAR modulators. A Bayesian model was generated based on 26-reported hCAR modulators and non-modulators (Supplementary Table S1) with protocols similar to previous publications (Pan et al , 2011; Pan et al , 2013). The model was generated with 70 physicochemical and structural descriptors including fingerprint ECFP-6 by using the “Create Bayesian Model” protocol embedded in DS 3.0 (Rogers et al , 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, the pharmacophore protocol embedded in Discovery Studio (DS) software suite (version 3.0; Accelrys; San Diego, CA) was used to generate a qualitative CAR pharmacophore based on 17 previously reported hCAR modulators. A Bayesian model was generated based on 26-reported hCAR modulators and non-modulators (Supplementary Table S1) with protocols similar to previous publications (Pan et al , 2011; Pan et al , 2013). The model was generated with 70 physicochemical and structural descriptors including fingerprint ECFP-6 by using the “Create Bayesian Model” protocol embedded in DS 3.0 (Rogers et al , 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that docking and pharmacophore-based virtual screening of chemical databases combined with cell-based biological assays are effective in identifying new compounds as modulators of nuclear receptors including hCAR (Pan et al , 2011; Lynch et al , 2013). Utilizing this combined approach, here, we have retrieved 144 compounds as potential hCAR activators by virtual screening of the Specs database (www.specs.net) based on their structure-activity features.…”
Section: Introductionmentioning
confidence: 99%
“…A number of drugs (eg, amlodipine, beclomethasone, megestrol, testosterone) can activate PXR, which induces several CYP isoenzymes responsible for metabolizing many drugs and some nutrients (47,48). Other substances (eg, bergamottin found in grapefruit juice) may also influence PXR (47). As more of the substances that can activate PXR are identified, their potential involvement in drug interactions, including DNIs, can be better predicted and prevented (47).…”
Section: Researchmentioning
confidence: 97%
“…The genetic expression of many metabolizing enzymes and some transporters is under the regulation of transcription factors such as pregnane X receptor (PXR). A number of drugs (eg, amlodipine, beclomethasone, megestrol, testosterone) can activate PXR, which induces several CYP isoenzymes responsible for metabolizing many drugs and some nutrients (47,48). Other substances (eg, bergamottin found in grapefruit juice) may also influence PXR (47).…”
Section: Researchmentioning
confidence: 98%
See 1 more Smart Citation